BREASTFEEDING FROM THE PERSPECTIVE OF TAFSIR AL-MUNĪR : ANALYSIS THE INTERPRETATION OF QS. AL-BAQARAH/2 : 233 - Monica Mulyana (Takafu: Journal of Tafsir and Gender Perspective, 2024)
The importance of the breastfeeding role for mothers. Not only for the growth and development of the baby but also for their health. However, some mothers are unable to breastfeed their children due to various factors, such as being working moms or having physical health issues. However, mothers who are unable to breastfeed their children are often criticized and even condemned, which creates a mental burden that disrupts the well-being of what should be a happy mother. This writing addresses the issue of the concept of breastfeeding mothers found in QS. Al-Baqarah/2: 233, which is deemed necessary to be understood in depth from the perspective of modern scholars, specifically Wahbah az-Zhuhaili in his Tafsir Al-Munīr.